Biomimetic artificial cartilage: fibre‐reinforcement of PVA hydrogel to promote biphasic lubrication mechanism. Issue 1 (26th February 2019) - Sakai, Nobuo; Yarimitsu, Seido; Sawae, Yoshinori; Komori, Mochimitsu; Murakami, Teruo
Abstract : The fibre‐reinforced structure in synovial articular cartilage plays an important role in enhancing the fluid load support in the biphasic lubrication mechanism. Poly(vinyl alcohol) (PVA) hydrogel is a potential biomimetic articular cartilage material. In this study, PVA hydrogel was reinforced with PVA fibres to improve its frictional properties. By computational analysis, the position of the PVA fibre layer was examined with a migrating contact condition to reduce the friction coefficient. To improve the fibre reinforcement, a method for fibre placement was developed to retain the initial strain of the fibre in the hydrogel matrix. The experimental results showed that the fibre‐reinforced PVA hydrogel with a surface fibre layer had a low friction coefficient of 0.031 in pure water. The fibre‐reinforced PVA hydrogel successfully reduced friction coefficient.